Gsk-3 β inhibitors mimic the cardioprotection mediated by ischemic pre- and postconditioning in hypertensive rats - González Arbeláez, Luisa Fernanda (2013)
The aim of this study was to examine the effects of GSK-3 inhibitors compared with PRE and POS in spontaneously hypertensive rats (SHR). Isolated hearts were submitted to the following protocols: IC: 45 min global ischemia (GI) and 1-hour reperfusion (R); PRE: a cycle of 5 min GI and 10 minutes of R prior to 45 min GI; POS: three cycles of 30 sec GI/30 sec R at the start of R. Other hearts received lithium chloride (LiCl) or indirubin-3 -monoxime,5-iodo-(IMI) as GSK-3 inhibitors. All interventions reduced the infarct size observed in IC group. The expressions of P-GSK-3 and P-Akt decreased in IC and were restored after PRE, POS, and GSK-3 inhibitors treatments. An increase of cytosolic MnSOD activity and lipid peroxidation and a decrease of GSH content observed in IC hearts were attenuated in PRE, POS, and LiCl or IMI treatments. An increase of P-GSK-3/VDAC physical association and a partial recovery of mitochondrial permeability were also detected after interventions. These data show that, in SHR hearts, GSK-3 inhibitors mimic the cardioprotection afforded by PRE and POS and suggest that a decrease in mitochondrial permeability mediated by P-GSK-3/VDAC interaction is a crucial event.